#BookTokMadeMeReadIt: young adult reading communities across an international, sociotechnical landscape. Issue 11 (30th November 2022) - Martens, Marianne; Balling, Gitte; Higgason, Kristen A.
Abstract : Purpose: This research article presents an exploratory case study of the sociotechnical landscape of BookTok, and how young people use it to connect with others around the books they love, or those they love to hate. By observing the interplay between young people, books, and the technology (TikTok) that connects them, this study aims to explore how blending analog and digital media tools makes reading social and fun. Design/methodology/approach: The authors selected three bestsellers available in English and Danish, and BookTokers who made related videos. This study used a qualitative, ethnographic (Pink, 2021) approach to explore interactions on the app. Inductive coding (Saldaña, 2021 ) helped the authors identify themes, and connect to areas of inquiry. Findings: During the pandemic, TikTok and BookTok offered young people opportunities for reading engagement in social, bookish communities by using technology to promote reading in print. In doing so, their actions made reading and being a reader highly entertaining. Research limitations/implications: As an exploratory case study, this research is not generalizable. But the findings will apply to future work on reading, publishing, and connected learning in a sociotechnical landscape. Practical implications: BookTok connects print and digital formats, offering innovative possibilities for young people's connected learning and reading promotion in schools and libraries. Originality/value: Because TikTok is a relatively new tool, and its sub-community BookTok became popular during the COVID-19 pandemic, research on this topic is still in its earliest stages.